Application of sensitivity analysis in self purification of the Surma River , Bangladesh - Islam, Shriful; Alam, Md. J.B.; Haque, Md. A. (BRAC University, 2011)
The rivers which flow through a city show an appreciable decline in water quality but they are often difficult to specify the exact cause of deterioration. Also the treatment of pollution of river is very troublesome. This study finds the treatment efficiency of the Surma River by its self purification capacity due to the pollution through discharges of choras (small canal), industrial wastewater discharges, and human excreta disposal. The sensitivity analysis by Streeter-Phelps Oxygen-sag equation is used to find the treatment efficiency and the corresponding sensitivity values for some selected pollution parameters were also determined. The Java software was used to find the treatment efficiency and to show the relation between treatment efficiency and those selected parameters.